Different supplements improve insulin resistance, hormonal functions, and oxidative stress on overweight and obese women with polycystic ovary syndrome: a systematic review and meta-analysis - Ren, Xiaoyan; Wu, Wenjuan; Li, Qiufan; Li, Wen; Wang, Xujuan; Wang, Gang (Frontiers in Endocrinology, 2024)
Objectives: To investigate various supplements that improve insulin resistance, hormonal status, and oxidative stress in overweight or obese women with PCOS. Methods: 25 RCTs evaluated the efficacy of various supplements in improving IR, hormonal status, and oxidative stress among overweight or obese women diagnosed with PCOS. Data extraction and analysis were carried out to determine the quality of the study's methodological design and the potential for bias. Results: A total of 25 RCTs were carried out, and 1636 women were enrolled. The SMD were as follows: For FPG, it was -0.34 (95% CI, -0.49 to -0.19, p = 0.123, I 2 = 30.8%); for insulin, it was -0.67 (95% CI, -0.83 to -0.52, p = 0.208, I 2 = 24%); for FI, it was -0.26 (95% CI, -0.52 to -0.00, p = 0.269, I 2 = 21.9%); for HOMA-IR, it was -0.59 (95% CI, -0.73 to -0.45, p = 0.015, I 2 = 48.7%); for HOMA-B, it was -0.51 (95% CI, -0.75 to -0.27, p = 0.547, I 2 = 0%); for QUICKI, it was 0.94 (95% CI, 0.76 to -1.12, p = 0.191, I 2 = 27.5%); for total testosterone, it was -0.61 (95% CI, -1.14 to -0.09, p = 0.00, I 2 = 78.5%); for testosterone, it was -0.38 (95% CI, -0.86 to 0.10, p = 0.03, I 2 = 71.5%); for FSH, it was 0.16 (95% CI, -0.08 to 0.40, p = 0.470, I 2 = 0%); for LH, it was -0.56 (95% CI, -1.32 to 0.20, p = 0.000, I 2 = 91.1%); for SHBG, it was 0.35 (95% CI, 0.02 to 0.69, p = 0.000, I 2 = 78%); for DHEAS, it was -0.27 (95% CI, -0.76 to 0.21, p = 0.001, I 2 = 78.7%); for TAC, it was 0.87 (95% CI, 0.45 to 1.30, p = 0.004, I 2 = 71.3%); for MDA, it was -0.57 (95% CI, -0.79 to -0.36, p = 0.992, I 2 = 0.0%).Conclusion: In comparison with a placebo, supplements have a favorable effect on IR, hormonal functions, and oxidative stress in PCOS.